Optimizing the Wet Fermentation of Ateng Coffee (Arabica) with the Addition of Yeast R1-TKSU and LAB (Leuconostoc suionicum) Inoculum - Sabatina, Grace; Astuti, Dea Indriani; Purwasena, Isty Adhitya (School of Life Sciences and Technology, Institut Teknologi Bandung, 2024)
Ateng coffee is an Arabica coffee that generally has a high selling value because of its better taste compared to other coffees. However, ateng coffee has poor post-harvest processing, resulting in low coffee quality and an impact on low coffee selling prices. In this study, optimization ofwet fermentation using yeast R1-TKSU and LAB (Leuconostoc suionicum) inoculums was used to improve the quality of ateng coffee. Treatment variations were fermentation with the addition of yeast, LAB, yeast : LAB 1:1, and there is also a control without the addition of inoculum. Sensory assessment showed that the best cupping score was the sample added by LAB with a total score of 86.5. The contents of malic acid, citric acid, lactic acid, sucrose, fructose, and glucose and ethanol which were analyzed by HPLC were found to be relatively stable ingreen coffee beans. Fermentation added inoculum affects the concentration of acetic acid. Amino acid analysed showed that overall the highest concentration of amino acids in green coffee beans was in the yeast : LAB 1:1 treatment. It can be concluded that controlled wet fermentation with the addition of yeast R1-TKSU and LAB (Leuconsotoc suionicum) inoculums can improve the quality of ateng coffee.